2017
DOI: 10.1111/jocn.13925
|View full text |Cite
|
Sign up to set email alerts
|

Older patients with late‐stage COPD: Their illness experiences and involvement in decision‐making regarding mechanical ventilation and noninvasive ventilation

Abstract: To provide competent care for these patients, healthcare personnel must be aware of how patients experience being seriously ill. Advanced care planning and shared decision-making should be initiated alongside the curative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(79 citation statements)
references
References 38 publications
1
75
0
3
Order By: Relevance
“…New knowledge and updated information about their disease made patients feel safer, and they dared to push themselves further. Other studies (Jerpseth et al, 2018;Russell et al, 2018) also found that patients with COPD have inadequate health competence about their illness. Some of the participants in our study emphasised that the lectures given by healthcare professionals during PR were too general and not particularly relevant to their disease.…”
Section: Discussionmentioning
confidence: 96%
“…New knowledge and updated information about their disease made patients feel safer, and they dared to push themselves further. Other studies (Jerpseth et al, 2018;Russell et al, 2018) also found that patients with COPD have inadequate health competence about their illness. Some of the participants in our study emphasised that the lectures given by healthcare professionals during PR were too general and not particularly relevant to their disease.…”
Section: Discussionmentioning
confidence: 96%
“…The studies were performed between 1992 and 2020 and mostly in an outpatient setting. Of the three qualitative studies, two [41,46] were performed in North America and the other [37] in Europe. All qualitative studies were conducted in an outpatient setting between 2011 and 2018.…”
Section: Key Characteristics Of the Included Studies And Participantsmentioning
confidence: 99%
“…Yet, despite its benefits, SDM is not common practice in all palliative care settings (Belanger, Rodriguez, & Groleau, 2011; Brom et al., 2017; Fitzsimons et al., 2019; Henselmans, Van Laarhoven, Van der Vloodt, De Haes, & Smets, 2017; Jerpseth, Dahl, Nortvedt, & Halvorsen, 2018). This may be for several reasons.…”
Section: Introductionmentioning
confidence: 99%